Apolipoprotein H drives hepatitis B surface antigen retention and endoplasmic reticulum stress during hepatitis B virus infection. (February 2021) - Liu, Yaming; Maiers, Jessica L.; Rui, Yajuan; Jiang, Xiaoming; Guleng, Bayasi; Ren, Jianlin
Graphical abstract: Model of APOH in attenuating HBV induced ER stress. HBV and LHBs upregulate expression of APOH, which interacts with HBV to inhibit the secretion of HBsAg. The intracellular retention of HBsAg promotes ER stress and activates the UPR as observed by increased expression of DDIT3 /CHOP and related genes. Our data shows that the interaction of APOH and HBV promotes ER stress through intracellular retention of HBsAg. Abstract: Background: Apolipoprotein H (APOH), also known as beta2-glycoprotein I (beta2-GPI), is an acute phase protein in hepatitis B virus (HBV) infection and binds to hepatitis B surface antigen (HBsAg) with high-affinity. APOH expression is upregulated by HBV and the large surface protein (LHBs), but also elevated in HBV-related hepatoma cells. Previous studies show that intracellular retention of HBsAg induces endoplasmic reticulum (ER) stress, a key driver of hepatocyte damage during chronic liver injury, but the mechanisms are unclear. We hypothesize that APOH mediates HBV-induced ER stress through increased retention of HBsAg. Methods: VR-APOH-myc and VR-LHBs-flag plasmids were constructed by PCR using pcDNA3.1(-)-APOH or an HBV expression vector, respectively. APOH and ER stress markers were examined at protein and mRNA levels by Western Blot or RT-qPCR. HBsAg titer was assayed by ELISA. RNA-seq was performed to elucidate the transcriptional impact of APOH manipulation in HBV-producing cells (HepG2.2.15 cells). Results: We found that HBV upregulates APOH expression in 293 T cells, and APOH overexpression subsequently inhibits secretion of HBsAg. Next, we show that LHBs overexpression in conjunction with APOH leads to ER stress in 293 T cells, as evidenced by production of the binding immunoglobulin protein (BiP) and C/EBP homologous protein (CHOP), as well as increased splicing of X-box binding protein 1 (XBP1). We further observed that loss of beta2-GPI reduced CHOP expression in HepG2.2.15 cells, while beta2-GPI overexpression enhanced CHOP production. Conclusion: The interaction of beta2-GPI and HBV initiates ER stress through driving intracellular retention of HBsAg and activates the UPR.